Efecto sobre la rentabilidad que tiene para el afiliado la comisión cobrada por las administradoras de fondos de pensiones - Medina Giacomozzi, Alex (2013)
The pension system in Chile is operated by private entities, called AFP, to which every worker must contribute 10% of their income on mandatory individual savings plans for retirement plus a variable fee to the direct benefit of the AFP. On the other hand, the employer quotes a percentage of worker's compensation insurance to fund disability and survivors through the AFP itself. The affiliate can freely choose the fund that will integrate its individual contribution, as the level of risk to take and the expected return to be obtained, among the five available funds. It is expected that the AFP achieves the highest possible return to their members with the commission charged by your management, but according to the results obtained, there is no evidence found to say conclusively that the commissions influence the behavior of the income of the various funds.